HAK PEKERJA ALIH DAYA JIKA TERJADI PERALIHAN PERUSAHAAN ALIH DAYA - Azzah Farah Nabilah; Dipo Wahjoeno (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2023)
Employers often ignore the rights of outsourced employees. Companies that use the services of workers often hire or deliberately outsource to lower labor costs, but the protection and working conditions offered are far from what is usual, which can put workers and the outsourced workers at risk. Unrest among employees is no doubt caused by this happening. Outsourcing is not specifically recognized as a practice under Law Number 13 of 2003 concerning Manpower. Law Number 11 of 2020 concerning Job Creation, which was recently passed, revised some of the provisions of Law Number 13 of 2003 concerning Manpower, one of which relates to provisions regarding outsourcing workers. However, it must be determined whether these structures provide sufficient legal protection for outsourced employees. Therefore, the authors are of the opinion that in order to fully understand the principle of legal certainty which will be discussed in this article, it is necessary to carry out analysis and research related to legal protection for outsourced workers